China's industrial revolution : - Andors, Stephen (Pantheon Books, 1977)
Framed by the premise that Maoist China essentially solved the problems of "bureaucracy" and "centralization," this is a particularized, enthusiastic account of state planning policies and plant management methods as they evolved away from the Soviet models of the 1950s. The 1966-67 Great Leap Forward is viewed as the first breakthrough in "putting politics in command" of technique, with its challenge to the monetary incentive system of labor relations and its replacement of one-man factory management with collective forms. For Andors, the Cultural Revolution represents the high point in this process, with Maoists overturning the "Seventy Articles" regulations on managerial duties. Among the upheavals were the Kiangsi Motor Vehicle Plant workers' shocked discovery that their manager relied on foreign models and imported equipment; attacks on the "elitist" attitudes of the experts running the 555 Clock Factory in Shanghai; and the revelation that the head technician at the Suchow Monosodium Glutamate Factory was a former landlord. Despite an abundance of such details, Andors shows little interest in the economic results of organizational shakeups; he does not justify industrial disruptions during the Cultural Revolution, but ignores them. Originally a doctoral dissertation, this entry in the Asia Library Series does not include enough material on the post-Cultural Revolution years to make it a supplement to Charles Bettelheim's Cultural Revolution and Industrial Organization in China (1974); it is a broad polemic against traditional socialist (Stalinist) methods and a specialized study of "the redistribution of power away from a technocratic elite.